Simple objective criteria for diagnosis of causes of acute diarrhoea on rectal biopsy. Issue 7 (July 1997) - Jenkins, D; Goodall, A; Scott, B B
Abstract : AIM: To identify simple, objective, accurate histological criteria for distinguishing acute infective-type colitis, chronic idiopathic inflammatory bowel disease, and irritable bowel syndrome on rectal biopsy in patients with acute onset diarrhoea at first presentation, one to 10 weeks after onset. METHODS: Cell counts and measurements of mucosal architecture were made on initial rectal biopsies from 18 patients with acute infective-type colitis, 17 patients with first acute presentation of chronic idiopathic inflammatory bowel disease, and 23 patients with irritable bowel syndrome. The data were analysed by ANOVA and discriminant analysis. RESULTS: Lamina propria cells were mainly in the upper third in irritable bowel syndrome patients. Increased lamina propria cellularity, mainly in the middle third, and numbers of crypt intraepithelial neutrophils distinguished acute infective-type colitis from irritable bowel syndrome in 93% of cases. Chronic idiopathic inflammatory bowel disease differed from irritable bowel syndrome and acute infective-type colitis in a decreased number of crypts and altered crypt architecture. Chronic idiopathic inflammatory bowel disease showed higher lamina propria cellularity, especially in the basal third, with an increased number of lamina propria neutrophils. On discriminant analysis, crypt numbers distinguished 86% of the cases of chronic idiopathic inflammatory bowel disease from the other groups. CONCLUSION: At one week or more from onset, acute infective-type colitis is characterised by a superficial increase in lamina propria cellularity, with only a slight increase in the number of polymorphs. At this stage, chronic idiopathic inflammatory bowel disease is characterised by a transmucosal increase in cellularity together with crypt loss and architectural abnormality. Thus, measurement of mucosal architecture establishes simple, accurate, objective criteria for routine biopsy diagnosis of chronic idiopathic inflammatory bowel disease from acute infective-type colitis and irritable bowel syndrome at initial presentation, one to 10 weeks after onset.